2013
DOI: 10.1128/jvi.02101-13
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A Binds to the Viral RNA and Replication Proteins, Resulting in Inhibition of Tombusviral Replicase Assembly

Abstract: Replication of plus-stranded RNA viruses is greatly affected by numerous host-encoded proteins that act as restriction factors. Cyclophilins, which are a large family of cellular prolyl isomerases, have been found to inhibit Tomato bushy stunt tombusvirus (TBSV) replication in a Saccharomyces cerevisiae model based on genome-wide screens and global proteomics approaches. In this report, we further characterize single-domain cyclophilins, including the mammalian cyclophilin A and plant Roc1 and Roc2, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…The published data support the model that binding of CypA and the plant orthologs to these viral components blocks the functions of the viral replication proteins in viral (+)RNA recruitment and VRC assembly (Figure 4) (Kovalev and Nagy, 2013). …”
Section: Characterization Of Antiviral Functions Of the Identified Cesupporting
confidence: 78%
“…The published data support the model that binding of CypA and the plant orthologs to these viral components blocks the functions of the viral replication proteins in viral (+)RNA recruitment and VRC assembly (Figure 4) (Kovalev and Nagy, 2013). …”
Section: Characterization Of Antiviral Functions Of the Identified Cesupporting
confidence: 78%
“…Members of the PPIase protein family (e.g., cyclophilins, FKBPs, and parvulins) are enzymes found in both eukaryotes and prokaryotes, participate in cell signaling, gene transcription and assist folding and localization of proteins, respectively (Hanes, 2015). More recently, Cyps were shown to facilitate dissociation of the human Papillomavirus Type 16 L1 and L2 capsid proteins from L2/DNA complexes following virus entry (Bienkowska-Haba et al, 2012), while CypA was shown to bind Tomato bushy stunt tombusvirus and inhibit tombusvirus replicase assembly (Kovalev and Nagy, 2013). Furthermore, Zhou et al (2016) showed that Cyp genes contribute to the development and virulence of Beauveria bassiana , an entomopathogenic fungus.…”
Section: Introductionmentioning
confidence: 99%
“…7), we suggest that the CypA and TPR-domain proteins and the WWdomain proteins have different regulatory roles during TBSV replication in yeast. This is surprising because, similar to the WW domain, the TPR domain of Cpr7p and CypA also bind to the RPR region in p33 responsible for viral RNA binding (77,78).…”
Section: Inhibition Of the Rna-binding And Protein-interaction Functimentioning
confidence: 92%
“…These were the TPR-domain-containing cellular proteins (77) and cyclophilins (45). The TPR domain from Cyp40-like Cpr7p chaperone and the CypA (homolog of the yeast Cpr1p) cyclophilin have been shown to bind to the tombusvirus replication proteins (45,65,78). Similar to the strategy described above with the WW-domain protein (Fig.…”
Section: Inhibition Of the Rna-binding And Protein-interaction Functimentioning
confidence: 94%